Among underserved children, behavioral self-regulation most consistently predicts early elementary teachers’ ratings of overall social–emotional learning - Cameron, Claire E.; Kim, Helyn; Doromal, Justin B. (Frontiers in Education, 2022)
The need for strengths-based perspectives on how children develop social–emotional learning (SEL) is especially pronounced in the context of research conducted with communities challenged by few resources and a history of oppression. This study included 313 underserved, primarily Black children who were assessed with several SEL building block measures at kindergarten entry. Specifically, we asked which SEL building blocks contributed to longitudinal teacher ratings of overall SEL on the Devereux Strengths and Skills Assessment (DESSA), collected four times during kindergarten and first grade. In separate models accounting for classroom membership, multiple kindergarten-entry SEL building blocks, including theory of mind, emotion, and situational knowledge, explained variance in teacher perceptions of children’s overall SEL at various time points after controlling for working memory and expressive vocabulary. In a single model that included all kindergarten-entry SEL building blocks, behavioral self-regulation most consistently predicted teachers’ overall SEL ratings over time. Even so, other SEL building blocks including theory of mind and emotion and situational knowledge should not be discounted because they also predicted variance in teacher-rated SEL at individual time points. A major implication of this study points to the importance of directly assessing building blocks of SEL at kindergarten entry, especially behavioral self-regulation, to effectively support children from underserved communities.